2019
DOI: 10.3389/fonc.2019.00715
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life in Advanced Non-small Cell Lung Cancer: A Methodological Appraisal Based on a Systematic Literature Review

Abstract: Background: The majority of lung cancer patients are diagnosed with advanced non-small cell lung cancer (NSCLC), the bulk of which receive palliative systemic treatment with the goal to provide effective symptom palliation and safeguard health-related quality of life (HRQoL). Advanced NSCLC trials with HRQoL endpoints face methodological constraints limiting interpretability. Objectives: We provide a comprehensive overview of recent clinical trials evaluating the impact of sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 149 publications
(73 reference statements)
3
17
0
2
Order By: Relevance
“… Bennett et al (2017) performed systematic review to explore the impact of SCLC on HRQL and the PROs used to capture this impact and conclude that paucity exists regarding the reporting on NSCLC HRQL outcomes. Likewise, Van Der Weijst et al (2019) performed a systematic literature review of clinical trials in NSCLC and conclude that while reporting HRQL data is important to support clinical decision-making as well as marketing authorisation and reimbursement decisions, the methodology of reporting HRQL remains poor. Among the instruments currently available to measure quality of life, primarily the EORTC QLQ-C30-LC13 ( EORTC, 2018 ), but also the Functional Assessment of Cancer Therapy-Lung (FACT-L) Scale ( FACIT, 1995 ) and its LC specific subscale FACT-LCS ( FACT-LCS, 1995 ) are the most commonly used instruments in LC clinical trials ( HallSinghal et al, 2019 ; King-Kallimanis et al, 2019 ; Van Der Weijst et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… Bennett et al (2017) performed systematic review to explore the impact of SCLC on HRQL and the PROs used to capture this impact and conclude that paucity exists regarding the reporting on NSCLC HRQL outcomes. Likewise, Van Der Weijst et al (2019) performed a systematic literature review of clinical trials in NSCLC and conclude that while reporting HRQL data is important to support clinical decision-making as well as marketing authorisation and reimbursement decisions, the methodology of reporting HRQL remains poor. Among the instruments currently available to measure quality of life, primarily the EORTC QLQ-C30-LC13 ( EORTC, 2018 ), but also the Functional Assessment of Cancer Therapy-Lung (FACT-L) Scale ( FACIT, 1995 ) and its LC specific subscale FACT-LCS ( FACT-LCS, 1995 ) are the most commonly used instruments in LC clinical trials ( HallSinghal et al, 2019 ; King-Kallimanis et al, 2019 ; Van Der Weijst et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Van Der Weijst et al (2019) performed a systematic literature review of clinical trials in NSCLC and conclude that while reporting HRQL data is important to support clinical decision-making as well as marketing authorisation and reimbursement decisions, the methodology of reporting HRQL remains poor. Among the instruments currently available to measure quality of life, primarily the EORTC QLQ-C30-LC13 ( EORTC, 2018 ), but also the Functional Assessment of Cancer Therapy-Lung (FACT-L) Scale ( FACIT, 1995 ) and its LC specific subscale FACT-LCS ( FACT-LCS, 1995 ) are the most commonly used instruments in LC clinical trials ( HallSinghal et al, 2019 ; King-Kallimanis et al, 2019 ; Van Der Weijst et al, 2019 ). Comparing our results to current LC specific scales (EORTC QLQ-C30-LC13 and FACT) reveals that the following side-effects and symptoms, observed in our study, are not included in all presently used HRQL specific LC scales: 1) skin conditions, 2) risk of infections, 3) sensory abnormalities, 4) increased weight, 5) autonomy/independence, 6) uncertainties regarding side-effects and (duration of) positive treatment outcomes, and 7) communication with healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These patient preference results are aligned with clinical trials that capture progression-free survival (PFS), objective response rates (ORR) and HRQoL. In addition to those clinical end points (PFS, ORR), which allow for assessment of the duration of tumor control and measurement of tumor shrinkage and tumor stabilization, HRQoL, a multi-dimensional concept, has become an integral end point in clinical trials for advanced cancer as it addresses the functional effect of a health status and/or a patient's treatment [28]. HRQoL-measured benefits have been shown to be consistent with the objective response benefits of ALK TKIs [29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the focus on the effect of treatment on wellbeing and functioning becomes increasingly important. It has been shown that lung cancer and its associated treatment indeed impacts health-related quality of life (HRQoL), they bring along several acute and late toxicities and may negatively affect neurocognitive functioning (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%